A review of Important Activities and Studies 1972-73 - Planning Commission (Planning Commission, 1973)
The report outlines the initiatives and recommendations made by various committees and task forces in India regarding power development, transport and communication, education, scientific research, housing, urban development, and water supply. It highlights the establishment of steering groups and task forces to address critical issues such as power shortages, urban transportation, educational development, and housing needs. The emphasis is on formulating strategies for the Fifth Five Year Plan, with a focus on improving infrastructure, enhancing power generation capacity, and addressing the needs of urban and rural populations. The reports and studies conducted by these groups aim to provide a comprehensive framework for future development in these sectors.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Power Development; Fifth Five Year Plan; Urban Transportation; Educational Development; Housing Needs; Scientific Research; Water Supply; Task Forces; Steering Groups; Infrastructure Improvement